Convergence of Vortex with Boundary Element Methods (Journal of Computational Mathematics, 1997)
In this work, the vortex methods for Euler equations with initial boundary value problem is considered, Poisson equations are solved using boundary element methods which can be seen to require less operations to compute the velocity field from the vorticity by Chorin$^{[6]}$. We prove that the rate of convergence of the boundary element schemes can be independent of the vortex blob parameters.